2022
DOI: 10.1007/s00062-022-01193-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comorbidity Burden and Polypharmacy on Poor Functional Outcome in Acute Ischemic Stroke

Abstract: Purpose Comorbidities and polypharmacy are risk factors for worse outcome in stroke. However, comorbidities and polypharmacy are mostly studied separately with various approaches to assess them. We aimed to analyze the impact of comorbidity burden and polypharmacy on functional outcome in acute ischemic stroke (AIS) patients undergoing mechanical thrombectomy (MT). Methods Acute ischemic stroke patients with large vessel occlusion (LVO) treated with MT fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Our findings also suggest that the presence of comorbidities was associated with the course of LSA after stroke—with higher LSA scores in those with fewer (0–1 vs ≥ 2) comorbidities. To the best of our knowledge, there are no previous reports on the association between comorbidities and life-space mobility in patients after stroke; however, comorbidities have repeatedly been shown to be prognostic of functional recovery, participation in life situations and survival post-stroke [ 4 , 47 50 ]. The presence of comorbidities in patients after stroke may affect life-space mobility through various biopsychosocial pathways; besides potentially causing additional physical, cognitive or perceptual deficits, they may also contribute to an increased psychological distress [ 51 ] as well as physical and mental fatigue [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest that the presence of comorbidities was associated with the course of LSA after stroke—with higher LSA scores in those with fewer (0–1 vs ≥ 2) comorbidities. To the best of our knowledge, there are no previous reports on the association between comorbidities and life-space mobility in patients after stroke; however, comorbidities have repeatedly been shown to be prognostic of functional recovery, participation in life situations and survival post-stroke [ 4 , 47 50 ]. The presence of comorbidities in patients after stroke may affect life-space mobility through various biopsychosocial pathways; besides potentially causing additional physical, cognitive or perceptual deficits, they may also contribute to an increased psychological distress [ 51 ] as well as physical and mental fatigue [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future work in pre-hospital and hospital settings should also consider combining physiological factors with other nonstroke characteristics which may have a bearing on thrombectomy outcome such as frailty, pre-stroke dependency and comorbidities (Adamou et al, 2022;Tan et al, 2022;Barow et al, 2023). Although some have been included in previously published thrombectomy outcome scores (Kremers et al, 2021), especially pre-stroke dependency, it has not yet been demonstrated that they are accurate when used by non-specialist practitioners making early triage decisions towards thrombectomy providers.…”
Section: Discussionmentioning
confidence: 99%
“…В одном из исследований, в котором для оценки мультиморбидности в острой стадии инсульта использовали модифицированный индекс Чарльсон, было показано, что неблагоприятные исходы возникали чаще у больных со значениями модифицированного индекса Чарльсон ≥2. Эта зависимость сохранялась при проведении многомерного регрессионного анализа [475]. В исследовании у больных с ишемическим инсультом высокая степень мультиморбидности (оценивали с помощью индекса Чарльсон) ассоциировалась с более высокими показателями госпитальной летальности [476].…”
Section: мозговой инсульт и коморбидностьunclassified